Electronic evidence in criminal proceedings - Singh, Nerisha (Department of Public Law, 2021)
The research question central to the thesis is stated as follows: what are the implications of new technological phenomena in South African law to the existing legal frameworks in relation to (i) investigatory powers of law enforcement and security and intelligence agencies to obtain electronic evidence, and (ii) its subsequent admissibility in criminal proceedings? Written with an emphasis on South African law, but also taking into account aspects of foreign and international law, the thesis seeks to investigate how our existing legal frameworks which regulate the use of and access to electronic evidence in criminal proceedings, including its admissibility, integrate and adapt to challenges raised by new and rapidly changing technological developments. The thesis provides a critical analysis of the existing legal framework regulating certain key investigative powers of law enforcement and security and intelligence agencies in the current modern environment of the information age in which they operate. Key among them is the Regulation of Interception of Communications and Provision of Communication-Related Information Act 70 of 2002. New technology has not only increased opportunities for criminal activity, it has also created opportunities for law enforcement and security and intelligence agencies to have access to more sophisticated and new capabilities. The range of intrusive capabilities now available to law enforcement and security and intelligence agencies triggers a range of issues and challenges for individual rights, including how those capabilities are used in investigation activities, the scale of their use, the extent to which such capabilities intrude on privacy rights, legislative authority for their use and safeguards that constrain and regulate such new technological capabilities. The challenges of regulating investigative powers in an era of new and fastpaced technological developments is explored in relation to (i) interception of communications (ii) acquisition and retention of communications data, and (iii) access to encrypted information. The introduction of electronic evidence in criminal legal proceedings raises unique challenges in the South African law on evidence. The most interesting perhaps is the extent to which the nature of the evidence presented, in this instance electronic evidence, impacts on admissibility in criminal proceedings. Potential anomalies arise as the relevant legislation, the Electronic Communications and Transactions Act 25 of 2002, is based on an electronic commerce model law concerned with commercial activities. In this regard, two separate issues are the focus of research interest. The thesis offers a rethinking of (a) admissibility of electronic evidence and (b) its weight. The meaning and application of certain statutory provisions, insofar as it applies to electronic evidence as hearsay or real evidence, or both, are key and controversial issues. Another relates to the business records exceptions, which directly translated for electronic records appears to have created a problematic presumption. On matters of evidential weight, there is no ‘one-size-fits-all' approach that will work. While a robust consideration of authentication is required in the court's assessment of evidential weight of electronic evidence, it should not be subject to inflexible tests that make it difficult for authentic electronic evidence to be admitted into evidence. A central premise of the thesis is that evolving technological phenomena can and do present challenges to existing legal concepts on evidence and the investigatory powers of law enforcement and the security and intelligence agencies to obtain electronic evidence and for its admissibility in criminal proceedings. This is done in the context of understanding whether South African law has developed appropriately in response to advancements in technology. In the final analysis, the thesis considers appropriate and meaningful reform towards a modern and transparent legal framework in South African law.